Qualitative Study in Identifying Factors Affecting the Behavior of Muslim Generation Y Towards Islamic Home Financing Products in Malaysia - Nik Mohd Fadhil Nik Mohammad; Siti Salwani Razali; Marhanum Che Mohd Salleh (USIM Press, 2024)
JMIFR Vol.18 No. 2 (Dec) 2021